Sagot :
[tex] \frac{2}{5} + \frac{1}{2} = \frac{(2)(2) + (1)(5)}{10} = \frac{4 + 5}{10} = \frac{9}{10} [/tex]
[tex] \frac{4}{9} - \frac{1}{3} = \frac{4 - 3}{9} = \frac{1 }{9} [/tex]
[tex] \frac{5}{12} + \frac{1}{6} = \frac{5 + 2}{12} = \frac{7}{12} [/tex]
[tex]4 \frac{3}{7} + 3 \frac{1}{2} = \frac{31}{7} + \frac{7}{2} = \frac{62 + 49}{14} = \frac{111}{14} \: or \: 7 \frac{3}{14 } \\ [/tex]
[tex]8 \frac{5}{7} - 5 \frac{2}{3} = \frac{61 }{7} - \frac{17}{3} = \frac{183 - 119}{21} = \frac{64}{21} \: or \: 3 \frac{1}{21} \\ [/tex]
#CarryOnLearning
#StudyWell
Answer:
1. 0.9
2.0.1111111
3.0.58
4 19.9
5 -5.19
Step-by-step explanation:
YAN PO ANG ANSWER
TAMA PO YAN